Interpreting the fossil evidence for the evolutionary origins of music - Wurz, S. (Southern African Humanities, 2009)
The adaptive history of two components of music, rhythmic entrained movement and complex learned vocalization, is examined. The development of habitual bipedal locomotion around 1.6 million years ago made running possible and coincided with distinct changes in the vestibular canal dimensions. The vestibular system of the inner ear clearly plays a role in determining rhythm and therefore bipedalism did not only make refined dancing movements possible, but also changed rhythmic capabilities. In current scenarios for the evolution of musicality, the descent of the larynx is regarded as pivotal to enable complex vocalization. However, the larynx descends in chimpanzees as well, for reasons unrelated to vocalization or bipedalism. A new perspective discussed in this paper is that vocal learning capabilities could have evolved from a simple laryngeal vocalization, or a grunt. The burgeoning literature on the neuroscience of musical functions is of limited use to investigate the origins of rhythmical and vocalization capabilities, but the out-of-proportion evolution of the cerebellum and pre-frontal cortex may be relevant. It suggested that protomusic was a behavioural feature of Homo ergaster 1.6 million years ago. Protomusic consisted of entrained rhythmical whole-body movements, initially combined with grunts.